Idioventricular rhythm complicating acute myocardial infarction. Issue 5 (September 1970) - Norris, R. M.; Mercer, C. J.; Yeates, S. E.
Abstract : The incidence, natural history, prognosis, and electrocardiographic characteristics of idioventricular rhythm complicating acute myocardial infarction are described. It occurred as a transient arrhythmia nearly always within 24 hours of infarction in 61 ( 8% ) of 737 patients, and was characterized by paroxysms of between 6 and 20 beats with widened bizarre QRS complexes at a rate of between 60 and 90 a minute. Most cases showed fusion beats and P waves dissociated from the QRS complexes, and in many cases idioventricular rhythm started during the slow phase of sinus arrhythmia. Though it usually occurred in patients with moderately severe transmural infarcts, the incidence of ventricular fibrillation and subsequent mortality was no greater than in patients with infarcts of equivalent severity who did not have idioventricular rhythm. It is concluded that this rhythm is a common and relatively benign arrhythmia complicating myocardial infarction, and that it should be distinguished from ventricular tachycardia .